Validity of student evaluation of teaching in higher education: a systematic review - Quansah, Frank; Cobbinah, Andrews; Asamoah-Gyimah, Kenneth; Hagan, John Elvis (Frontiers in Education, 2024)
Introduction Data obtained from students regarding the quality of teaching are used by higher education administrators to inform decisions concerning tenure, promotion, course development and instructional modifications, among others. This article provides a review regarding studies conducted to examine the validity of student evaluation of teaching, specifically focusing on the following objectives: (1) identify the context where studies have been conducted on student evaluation of teaching; (2) find out the methodologies usually employed for assessing the validity of student evaluation of teaching; and (3) establish the sources of measurement error in student evaluation of teaching. Methods The systematic review was conducted based on the PRISMA checklist. The databases searched include Scopus, Web of Science (WoS), Google Scholar, PubMed, MEDLINE, ERIC, JSTOR, PsycLIT, EconLit, APA PsycINFO and EBSCO using some specific keywords. After applying the four eligibility criteria, 15 papers were left to be analyzed. Results It was discovered that the generalizability theory approach was mostly used to understand the validity of student evaluation data. The review revealed that students were found at the centre of inconsistencies in the evaluation process. Discussion The general impression from the review is that the credibility and validity of teaching evaluation outcomes is questionable, considering the several sources of errors revealed. The study recommended closely studying these sources of errors (e.g., rating behaviours of students).